Biogenesis of membrane-bound and secreted immunoglobulins: two primary translation products of the human delta chain, differentially N-glycosylated to four discrete forms in vivo and in vitro. - McCune, J M (1981)
Structural differences between the heavy chain of membrane IgD (delta m) and the heavy chain of secreted IgD (delta s) were investigated by using a human lymphoblastoid cell line that expresses idiotypically identical IgM and IgD. In a wheat germ cell-free system, mRNA from this cell line was shown to encode two distinct delta chains that differed in molecular weight. When translated in vitro in the presence of dog pancreatic microsomal membranes or when synthesized in vivo, these two delta chains were processed to four discrete glycosylated forms, all of which shared idiotypic determinants, C region determinants, and light chain linkage. As shown by digestion with endo-beta-N-acetylglucosaminidase H, these four delta forms represent two delta polypeptide chains that are differentially N-glycosylated. Pulse-chase experiments demonstrated that, after endo-beta-N-acetylglucosaminidase H treatment, delta m has a higher molecular weight than delta s. After integration into dog pancreatic microsomal membranes in vitro, delta m was found not to have a large cytoplasmic domain exposed to proteolytic digestion. The finding that delta m and delta s differ in primary structure is analogous to previous work with the corresponding heavy chains of IgM (mu m and mu s) from the same cell line. Thus, this cell line produces four Ig heavy chains (mu m, mu s, delta m, and delta s), with the same idiotype. The observation of differential N-glycosylation, apparently unique for the delta class, is discussed.